Understanding adolescent girls’ experiences with accessing and using contraceptives in Zambia - Mumbi Chola; Khumbulani Hlongwana; Themba G. Ginindza (BMC Public Health, 2023)
Abstract Background Globally, the unmet need for contraception among adolescent girls is high and is driven by barriers to access and utilisation of contraceptives. Understanding adolescent girls’ experiences with accessing and using contraceptives is crucial because it influences their decision to use and willingness to continue using health products and services. While determinants of contraceptive use have been extensively researched globally, few studies explore how adolescent girls experience contraceptive use in Zambia using qualitative methods. Therefore, this study aimed to understand Zambian adolescent girls’ experiences using contraceptives. Methods Thematic analysis was used to analyse data generated from 7 focus group discussions and three in-depth interviews with adolescent girls aged 15 to 19 years in 4 districts in Zambia. NVivo version 12 pro (QSR International) software was used to manage and organise the data. Results Results revealed that adolescents’ experiences concerning contraceptives across the continuum of care are shaped by various factors, including knowledge of contraceptives which comprises sources of information and contraceptives; experience with using contraceptives, challenges with access to contraceptives, and misconceptions about contraceptives; perspectives about existing contraceptives; and preferred types of contraceptives. Conclusion The multifactorial interaction relating to adolescents’ personal experience, their community and the environment in which they access contraceptive services all contribute to their overall experience and influence their contraceptive decisions. Therefore, qualitative studies exploring adolescents’ experiences with accessing and using contraceptives are vital for tailoring interventions responsive to the contraceptive needs of this age group.